Multiterminal Hybrid DC Line Protection Based on Intrinsic Mode Energy Entropy - Xing, Chao; Li, Pengsong; Bi, Guihong; Chen, Shilong; Chen, Junhao; Zhang, Zihang (Frontiers in Energy Research, 2022)
In view of the UHV multiterminal hybrid DC transmission system, the DC line protection with universal applicability, fast response speed, stability, and reliability is particularly important for its safe and economic operation. In this article, the boundary frequency characteristics of the UHV multiterminal hybrid DC transmission system are analyzed by considering the DC boundary of the rectifier side and inverter side, line frequency variation, and other factors. According to the fact that the boundary of the fault line has a strong attenuation effect on the high-frequency component of the transient current, a protection method based on the intrinsic mode energy entropy is proposed to distinguish the faults inside and outside. The criterion to initiate the protection is constructed by using the amplitude of the transient power; the fault direction criterion is constructed by using the positive and negative characteristics of the transient energy of the fault power detected by power direction elements on both sides of the T-zone; the fault pole selection criterion is constructed by using the ratio of low-frequency transient power changes of positive and negative poles. Finally, the Kun–Liu–Long line UHV three-terminal hybrid DC transmission system model is built on the PSCAD/EMTDC simulation platform, and a large number of simulation examples verify that the protection can operate reliably under different fault poles, fault positions, and transition resistances.